Dissemination of Lithuanian Literature: Becoming Part of World Literature - Maskaliūnienė, Nijolė (Literatūra, 2021)
The article discusses the policy of dissemination of national literature abroad as one of the soft power practices used for the formation of the image of the country and the country’s literature, created through the translated and published works of Lithuanian authors in foreign languages. It also reviews the current situation, the selection of the works to be translated, institutions and bodies in charge of this dissemination, and problems of the research on the reception of the works (authors) translated into foreign languages.